The Effect Of Various Carbonization Temperature And Duration On The Food Using Microwave Food Waste Carbonizer - Chia, Yong Ham (Universiti Sains Malaysia, 2018)
Food waste is one of the challenges faced by the world’s food system. Food waste is also a type of biomass which can become a valuable resource when it is managed reasonably and effectively, whilst reducing the impact on the environment. There are many ways to treat the food waste, one of the method is microwave carbonization. The microwave carbonization of biomass is one of the novel thermochemical process in which biomass is irradiated with microwave and the biomass eventually will convert to other resources such as biochar or biogas. In this study, temperature of 260°C - 340°C and carbonization duration of 30mins and 1hour will be used. A microwave oven has been modified and is used as a carbonizer to conduct the experiment and potatoes are used as specimen for the experiment. The products formed from different carbonization temperatures and durations are observed and compared. Most of the potatoes of one-hour carbonization time are fully carbonized whereas for those of 30 mins duration, the potatoes were not fully carbonized. Besides that, the heating values for the products are analyzed and compared. The heating values calculated show an increasing trend as the carbonization temperature increase.